PENGEMBANGAN BUKU AJAR PERKULIAHAN KONSEP DASAR PENDIDIKAN IPS SD UNTUK MAHASISWA PGSD - M. Anggrayni; Wiwik Okta Susilawati; Lika Apreasta (Study program PGSD FKIP Universitas Bung Hatta, 2023)
A lecturer's lack of ability to develop learning books in lectures means that lectures only use the same textbooks. This research produced a product in the form of a lecture textbook on Basic Concepts of Elementary School Social Sciences Education. Research and development was carried out by adapting the model from Dick & Carey (1996) with all the ADDIE stages. Based on the results of research conducted by researchers, the results show that the textbooks for the Basic Concepts of Elementary School Social Sciences Education that have been developed meet valid, practical and effective standards. Digital textbook products that meet valid standards can be seen in the average results of each validation. Material validation with an average of 92.2% is classified as very valid, media validation with an average of 94% is classified as very valid and language validation with an average of 92.7% is classified as very valid. Then, for digital textbook products that are classified as practical, we can see from the assessment results of course lecturers (100%) and students (98.25%) that they are classified as very practical. Furthermore, the product is very effective because student learning outcomes from the cognitive aspect are above the predetermined standards (100% complete).